PENERAPAN AKUNTANSI PERSEDIAAN PITA CUKAI (PSAP 05) PADA KPPBC TMP B PEKANBARU - Renza, Abdel; Herdiyana, Deni (FEB-UP Press, 2024)
The research was conducted to analyze the implementation of excise stamp inventory accounting and compare government accounting standards regarding excise stamps (PSAP 05) with the implementation carried out by KPPBC TMP B Pekanbaru. The research method used is a qualitative approach, namely literature study, observation, and interview. The conclusion of the research is that in general the practice of classifying, recognizing, measuring, recording, presenting and disclosing inventory accounting refers to applicable regulations. However, the management of excise stamp transactions should be simplified and there needs to be integration of information systems so that business processes can be faster and more efficient and transaction recording can be carried out simultaneously using the perpetual method in accordance with applicable regulations.